The market impact of high-frequency trading systems and potential regulation. Issue 1 (2nd January 2017) - Klaus, Tim; Elzweig, Brian
Abstract : As transaction costs of trades have decreased, there has been a large growth of high-frequency trading in markets around the world. Although there are benefits that high-frequency trading brings to both the market and individual companies, there are negative and controversial aspects as well. This paper addresses high-fequency trading strategies, systems, and controversies, and then analyzes current and potential laws and regulations and their impacts on the marketplace.